Immune-related adverse events with renal colic as the main manifestation: a case report of sintilimab-induced ureteritis/cystitis treated by ureteral stent and review of the literature - Ji, Jiaxiang; Lai, Chin-Hui; Zhang, Xiaowei; Hu, Hao (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of systemic cancer therapy. During disinhibiting the antitumor responses of immune system, ICIs may also cause unique immune-related adverse events (irAEs) which could affect any organ. Here, we report a rare case of sintilimab-induced ureteritis/cystitis in a 55-year-old male undergoing neoadjuvant chemo-immunotherapy for gastric cancer. The patient presented with severe renal colic, hematuria, and hydronephrosis. Antibiotic antispasmodic and nonsteroidal anti-inflammatory drug treatment failed to alleviate symptoms. The application of corticosteroid was negated for recent extirpative surgery under plan. Bilateral ureteral stenting effectively resolved the pain and improved renal function. The patient later successfully underwent laparoscopic radical gastrectomy with significant tumor regression in postoperative pathology. This case highlights ureteral stenting as a potential corticosteroid-free treatment option for ICI-induced ureteritis/cystitis.